AWARENESS OF STROKE, KNOWLEDGE OF STROKE RISK FACTORS AND THEIR PREVALENCE AMONG THE POPULATION OF 18+ IN THE SOUTHWESTERN REGION OF NORTH MACEDONIA - Vojtikiv Samoilovska, Danijela; Bozinovska, Maja; Arsovska, Anita; Efremov, Ljupco; Dolenc, Jovanka Sion; Lickova, Elena; Kozlovska, Rodna; Trajkovska, Suzana; Zikova, Sanja (Journal of Morphological Sciences, 2022)
Reduction in the risk of stroke and increase in the speed of hospital presentation, after the onset of stroke, depend on the level of knowledge of stroke in the general population. The aim was to assess: community knowledge of stroke symptoms and risk factors,  information resources, as well as self-reported prevalence of established risk factors,  among 18 +  population. Materials and metods :cross-sectional study was conducted   by members of the  Association for fight against stroke- â€œMozocen Udar Ohridâ€,   through face to face  and  telephone interviews,   in the period of March 2019 to April 2021. In total  576 respondents, older  than 18, residents of Southwest region of our country.  Results: 48% of them are up to 49 years,  52 % are older than 50 years.  The most reconaised stroke risk factors were:  hypertension (38%) ,  smoking (17%), stress (15%) and lipids (13%). 44% of the respondents didnâ€™t mention any stroke risk factor. 46%  respondents  donâ€™t know how to recognize stroke.  29% of them   mentioned paralysis on part of the body, 22% speech problems  and 14 % face paralysis. Main source of information for stroke is internet,  mentioned by 42%. 42 %  stated that have  hypertension, 33% stated high level of triglycerides, 25%  stated that they have 1-6 drinks  per week, 20% stated that they were inactive in last week . Conclusion: A community-based education program to increase public knowledge of stroke   should be considred, internet and TV are  powerful tools. Key words: stroke, risk factors, public knowledge.